AKUNTABILITAS PEMERINTAH DESA DALAM PENGELOLAAN ALOKASI DANA DESA (ADD) (STUDI PADA DESA PASSI KECAMATAN FATULEU TENGAH KABUPATEN KUPANG) - Yuningsih Nita Christiani (Universitas Nusa Cendana, 2016)
This research was focusing on principal of accountability in the management of the village fund(Alokasi Dana Desa/ADD). The purpose of this study is to analyze and describe the accountabilityof the Government of the village, the supporting factors and the barrier as well as the challenges facedby the apparatus as stakeholder to manage the ADD, in the village of Passi in Fatuleu Tengahduring the year of 2015. The village of Passi is one of the villages getting allocation of ADD lessthan three (3) other villages located in the subdistrict of Fatuleu Tengah. Result of research showedthat the apparatus of the village had already accountable and transparent in financialaccountability, however it had not yet to be matched with government policy in the using of budget.Keywords : Accountability, Alokasi Dana Desa (ADD)